A Modern Approach to the Treatment of Delayed Eruption of Upper Permanent Canines (Literature Review) - Lykhota, К. М.; Yakush, О. Г. (Actual Dentistry, 2025)
Introduction. Teething is a physiological process that occurs in a sequence established by nature to perform one of the main functions: chewing. However, in some cases, this mechanism fails or is interrupted, leading to the absence of a tooth or teeth, usually the upper canines, which are fundamental to the patient’s esthetics, harmonious smile and stomatogenic system. Orthodontic treatment of affected maxillary canines remains a problem for modern clinicians. Orthodontists often face many complications in the treatment of this pathology, which has a prevalence of approximately 1% to 6%. Delayed canine eruption is 2-3 times more common in women than in men. Purpose: based on the analysis of literary sources, to determine the main modern approaches to the treatment of delayed eruption of upper permanent canine. Materials and methods. Information search and analysis of scientific sources was carried out using scientometric databases Web of Science, PubMed, Google Scholar over the past 15 years. Conclusion. The analysis of literature sources showed that research on the treatment of impacted canines is extremely important due to the complexity and variety of approaches that include surgical, orthodontic, periodontal and restorative methods. Early detection and timely intervention are key factors that influence treatment success and can significantly reduce overall costs and duration of therapy. The study of various treatment methods and their effectiveness will allow to develop optimal strategies for each specific case, taking into account the patient’s age, anatomical features and clinical condition.